Experiments and Simulation on Mannesmann Piercing Process in the Drill Steel Manufacture - Zhao, Y.Q.; Mao, J.H.; Liu, F.F.; Mac, Zh.H. (Проблемы прочности, 2015)
Steel drill rods are employed in the mining industry to drill blast holes in rock, for them a high-quality metal surface and accurate geometrical parameters are essential. Drill steel is a special material exclusively designed for drill rods. To estimate the microstructure and dimensional stability of drill steel, a rigid plastic finite element method (FEM) was applied in examining the Mannesmann piercing in the drill steel manufacture. The three-dimensional thermal-force coupling FEM models were computer-generated with different plug positions.